Safety II professionals: How resilience engineering can transform safety practice. (March 2020) - Provan, David J.; Woods, David D.; Dekker, Sidney W.A.; Rae, Andrew J.
Highlights: Safety management approaches can be categorised as either a mode of centralised control or a mode of guided adaptability. Safety professionals and their organisations are focussed on a safety management mode of centralised control and this can be detrimental to safety. Resilience engineering, safety II and safety differently offer an alternative approach to safety management that resolve the shortcomings in traditional approaches to managing safety in complex systems. This paper provides the first practical description of the purpose, tasks and activities of a safety professional through the theoretical lens of resilience engineering and safety II. Abstract: The safety management literature describes two distinct modes through which safety is achieved. These can be described as safety management through centralized control, or safety management through guided adaptability. Safety management through centralized control, labelled by Hollnagel as 'Safety-I', aims to align and control the organization and its people through the central determination of what is safe. Safety management through guided adaptability, or 'Safety-II', aims to enable the organization and its people to safely adapt to emergent situations and conditions. Safety-II has been presented as a paradigm shift in safety theory, but it has created practical difficulties for safety professional practice. In this paper, we define the two modes of safety management and explain the challenges in changing the role of a safety professional to support Safety-II. When should safety professionals re-enforce alignment, and when should they support frontline adaptations? We outline specific activities for safety professionals to adopt in their role to move towards a guided adaptability mode of safety management. This will move the safety professional further towards their fundamental responsibility – 'to create foresight about the changing shape of risk, and facilitate action, before people are harmed.'